Cross-Cultural and Language Understanding of IAIN Takengon Students - Putri Shafira; Wulandari Siregar; Sirmi Rezeki; Muhammad Hasyimsyah Batubara (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2022)
Understanding culture and language is a communication instrument that is often used in communicating with other people, especially when we speak a foreign language with foreigners. Good communication will be seen when we talk with good words. This study is to know the understanding of 6th and 2nd-semester students regarding cross culture and language. The research used a qualitative descriptive method with an observation and interview approach for 6th and 2nd-semester English Language Study Program students at IAIN Takengon. The results that can be concluded show that students' understanding of cross-cultural language is in a position of knowing enough. Students in semesters 2 and 6 believe that communication is important, culture is important, and language is also essential to learn and understand. Because learning culture, and a foreign language makes it easier to communicate with foreigners, not only easy but allows us to not have any complications with people because of the misunderstanding of other people's cultures.